EXPERIMENTAL INVESTIGATION OF DYNAMIC PROCESSES IN AN ELECTROPNEUMATIC POSITIONING SYSTEM WITH HIGH SPEED VALVES AND PWM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper presents a demonstration experimental test bench for investigating the dynamic characteristics of an electropneumatic positioning system with High Speed Pneumatic Valves (HSPV) and Pulse Width Modulation (PWM) control. A specialized virtual instrument has been developed for real-time control, data acquisition, and processing. The transient response of the electropneumatic positioning system is examined under various single-step input signals with frequencies ranging from 30 Hz to 70 Hz and varying duty cycles from 30% to 90%. The results are presented graphically, demonstrating that the system exhibits better linear characteristics compared to conventional pneumatic actuation systems.